C-Reactive Protein and High-Sensitive Cardiac Troponins Correlate with Oxidative Stress in Valvular Heart Disease Patients. (30th April 2022) - Jan, Muhammad Ishtiaq; Khan, Riaz Anwar; Fozia,; Ahmad, Ijaz; Khan, Naeem; Urooj, Komal; Shah, Azhar Ul Haq Ali; Khan, Asif Ullah; Ali, Tahir; Ishtiaq, Ayesha; Shah, Muhib; Ullah, Anwar; et al.
Abstract : Background . Valvular heart disease (VHD) is a major contributor to loss of physical function and longevity. Oxidative stress is one of the key causative factors involved in heart disease including VHD. Here, we aimed to illuminate the role and relation of oxidative stress to the VHD risk markers in the human population. Materials and Methods . 150 VHD patients and 103 healthy individuals as control were selected for the study and were divided into three groups: the aortic valve, mitral valve, and combined disease based on valvular calcification. Results . Our results demonstrated enhanced oxidative stress in the VHD condition, as we found elevated levels of reactive oxygen species (ROS) at the serum, supported by an increased level of thiobarbituric acid reactive substances (TBARs) in the cardiac valvular tissues of the VHD patients. In contrast, we experienced declined antioxidants including Super Oxide Dismutase (SOD), catalase (CAT), and peroxidase (POD) activities. Concurrently, increasing levels of C-reactive protein (CRP), high-sensitivity cardiac troponin I (hs-cTnI), and high-sensitivity cardiac troponin T (hs-cTnT) were detected in the aortic, mitral, and combined disease condition, suggesting a key association of oxidative stress to VHD conditions. Furthermore, regression analysis validated a key association between the impairment of the redox system (ROS and antioxidant enzyme activities) and VHD condition. Conclusion . Taken together, dysregulated oxidative stress contributes to the progression of VHD via positively correlating with CRP, hs-TnI, and hs-TnT level.